2020
DOI: 10.3390/ijms21197314
|View full text |Cite
|
Sign up to set email alerts
|

Roles of ASYMMETRIC LEAVES2 (AS2) and Nucleolar Proteins in the Adaxial–Abaxial Polarity Specification at the Perinucleolar Region in Arabidopsis

Abstract: Leaves of Arabidopsis develop from a shoot apical meristem grow along three (proximal–distal, adaxial–abaxial, and medial–lateral) axes and form a flat symmetric architecture. ASYMMETRIC LEAVES2 (AS2), a key regulator for leaf adaxial–abaxial partitioning, encodes a plant-specific nuclear protein and directly represses the abaxial-determining gene ETTIN/AUXIN RESPONSE FACTOR3 (ETT/ARF3). How AS2 could act as a critical regulator, however, has yet to be demonstrated, although it might play an epigenetic role. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 129 publications
(260 reference statements)
0
23
0
Order By: Relevance
“…Auxin locally repressed the expression of class-I KNOTTED-LIKE HOMEOBOX ( KNOXI ) genes, which are responsible for stem cell maintenance in the SAM, like SHOOTMERISTEMLESS ( STM ) and BREVIPEDICELLUS ( BP ) [ 101 , 115 ]. ARP genes (including ASYMMETRIC LEAVES 1 ( AS1 ), ROUGHSHEATH 2, and PHANTASTICA ) like AS1 interact with ASYMMETRIC LEAVES 2 (AS2), and their protein complexes bind directly to the promoter of KNOXI genes and repress their expression [ 116 , 117 , 118 ]. The formation of an auxin gradient within the SAM also contributes to the formation of boundary domains that separate primordia from the rest of the meristem [ 114 ].…”
Section: Mechanisms Of Leaf Development: the Gene Regulatory Netwomentioning
confidence: 99%
See 1 more Smart Citation
“…Auxin locally repressed the expression of class-I KNOTTED-LIKE HOMEOBOX ( KNOXI ) genes, which are responsible for stem cell maintenance in the SAM, like SHOOTMERISTEMLESS ( STM ) and BREVIPEDICELLUS ( BP ) [ 101 , 115 ]. ARP genes (including ASYMMETRIC LEAVES 1 ( AS1 ), ROUGHSHEATH 2, and PHANTASTICA ) like AS1 interact with ASYMMETRIC LEAVES 2 (AS2), and their protein complexes bind directly to the promoter of KNOXI genes and repress their expression [ 116 , 117 , 118 ]. The formation of an auxin gradient within the SAM also contributes to the formation of boundary domains that separate primordia from the rest of the meristem [ 114 ].…”
Section: Mechanisms Of Leaf Development: the Gene Regulatory Netwomentioning
confidence: 99%
“…During this process, KNOXI genes are expressed in the boundary region and CUC genes, which are negatively regulated by miR164, have positive feedback with KNOXI [ 136 , 137 ]. KNOXI and AS1 appear to be involved in the proximal-distal polarity patterning, and BLADE ON PETIOLE ( BOP ) genes, such as BOP1 and BOP2 , are expressed in the proximal region, directly repressing KNOXI or indirectly restricting the location of KNOXI by activating AS2 [ 118 , 138 , 139 ]. In addition, ARF3/4 genes also repress KNOXI to promote organogenesis at the shoot apex [ 140 ].…”
Section: Mechanisms Of Leaf Development: the Gene Regulatory Netwomentioning
confidence: 99%
“…The AS2 gene was identified and its genetic, molecular, and cellular biological roles in leaf development have been intensively investigated for over 20 years (Iwakawa et al 2002(Iwakawa et al , 2007(Iwakawa et al , 2020Machida et al 2015;Semiarti et al 2001). Transcription of AS2 starts at the globular stage of embryogenesis, and its transcripts are accumulated in protoderm cells on the adaxial side of cotyledonary primordia at the heart stage (Iwakawa et al 2002).…”
Section: Repressive Controls Of Abaxial-determining Arfs and Class 1 Knoxs By As2 And As1 Are Critical For The Development Of Flat Symmetmentioning
confidence: 99%
“…Molecular and genetic analyses of the AS2 gene in Arabidopsis thaliana have shown that it is a key regulator for the development of flat symmetric leaves containing vascular bundles and fine networks of venation systems, the morphology of which seems to be evolved suitably for efficient photosynthesis (Fig. 1 a) (Byrne et al 2000 ; Ikezaki et al 2010 ; Iwakawa et al 2020 ; Machida et al 2015 ; Ori et al 2000 ; Semiarti et al 2001 ; Serrano-Cartagena et al 1999 ). The as2 mutant generates shorter petioles, leaf lobes, and leaflet-like protrusions from the petioles of leaves in a bilaterally asymmetric manner (Fig.…”
Section: Genetic Roles Of As2 As1 and Modifier Genes In Leaf Developmentmentioning
confidence: 99%
“…PHANTASTICA (PHAN), encoding an MYB domain transcription factor, was first associated with adaxialabaxial polarity in Antirrhinum majus [4,5]. In Arabidopsis, ASYMMETRIC LEAVES 1 (AS1), a homolog of PHAN, regulates leaf adaxial polarity, forming a protein complex with the plant-specific lateral organ boundaries (LOB) family protein AS2 [6]. Another 2 of 13 three members of the HD-ZIP III (Class III homeodomain-leucine zipper) gene family, including PHABULSA (PHB), PHAVOLUTA (PHV), and REVOLUTA (REV), have also been associated with leaf-rolling phenotype in Arabidopsis [7,8].…”
Section: Introductionmentioning
confidence: 99%